Розв’язність першої крайової задачі для рівняння теплопровідності з нелінійними джерелами і сильними степеневими особливостями - Чмир, О.Ю. (Український математичний журнал, 2013)
С помощью принципа Шаудера и принципа сжатых отображений исследован характер точечных степенных особенностей решения первой обобщенной краевой задачи для уравнения теплопроводности с нелинейными краевыми условиями. Установлены достаточные условия разрешимости этой задачи. By using the Schauder principle and the principle of contracting mappings, we study the character of point power singularities for the solution of the generalized first boundary-value problem for the heat-conduction equation with nonlinear boundary conditions. We establish sufficient conditions for the solvability of the analyzed problem.